2016
DOI: 10.1039/c6gc02706g
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed one pot synthesis of hydroxymethylated triglycerides

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…These findings are also supported by recently shownr esults in ap arallel work. [42] To investigate the influence of solvents, polar protic solvents were used in this reaction and the hydroformylation activity was slightly inhibited, leading to am ix of TCD-dialdehyde 4 and TCD-diol 6 (entry 1.7-1.8). With polar aprotic solvents, only TCD-monoaldehyde 2 was obtained (entry 1.9-1.10) indicating that strong coordinating solvents, such as acetonitrile, have as trong binding character to the rhodium centre and deactivate the catalyst for the second hydroformylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are also supported by recently shownr esults in ap arallel work. [42] To investigate the influence of solvents, polar protic solvents were used in this reaction and the hydroformylation activity was slightly inhibited, leading to am ix of TCD-dialdehyde 4 and TCD-diol 6 (entry 1.7-1.8). With polar aprotic solvents, only TCD-monoaldehyde 2 was obtained (entry 1.9-1.10) indicating that strong coordinating solvents, such as acetonitrile, have as trong binding character to the rhodium centre and deactivate the catalyst for the second hydroformylation.…”
Section: Resultsmentioning
confidence: 99%
“…Dependingo nt he size or sterical properties of the used amines, the capacity to form alcohols differs as with parallels tudies. [42] To further simplify the method, experiments in pure amine were performed at 70 bar.I tcould be shown that the reaction sequence is still feasible with 29 %y ield after 4h and 64 % yield after 16 hr eactiont ime for the desired diol 6 (Entry 1.12,1.13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Most of the reactions on oleochemicals occura tt he fatty acidc arboxy groupa nd they are comparatively few examples on the alkyl chain.H owever,t he presence of double bond(s) in unsaturated fatty acid derivatives allows the installation of arange of organic functions [5] including aldehyde, [6] epoxide, [7] diol, [8] ketone and diketone, [9] ahydroxyketone, [10] carbonate, [11] among others. [12] More importantly,c leavage reactions-mainly using methylo leate as the archetype-can give access to building-blocksw ith higher added value, essentially for surfactants and polymer applications. In this respect, the formation of fatty mono-a nd difunctionalized aldehydes is of great interesta st hey can be used for ab road variety of transformations.…”
Section: Introductionmentioning
confidence: 99%